The figure of the amicus curiae in the field of constitutional justice - Bazán, Victor (2021)
This study investigates the current profiles of the amicus curiae and its importance in the deployment of constitutional justice. Also analyzes its usefulness as an instrument of viability of citizen participation in the judicial debate around issues of social and institutional interest, and evaluates its qualitative contribution to the lines of reasoning of the domestic and international human rights courts, on the basis of growth opportunities for interaction of Constitutional Law, Constitutional Procedural Law and International Human Rights Law.